The last smallpox outbreaks in the world – eradication efforts in Somalia – selected memories of a WHO field epidemiologist. - Hanson, Stefan (Somali Health Action Journal, 2024)
Somalia was the last country in the world with smallpox. The government tried to control smallpox through mass vaccination in the 1970s. This was not successful. Contributing to this was a nomadic, highly mobile population and resistance to vaccination. The low vaccination coverage led to importations from neighboring countries, Kenya and Ethiopia and increased transmission inside the country. There was a major outbreak in Mogadishu in August 1976, which continued up to January 1977. It was followed by additional outbreaks in the south of the country, mainly in the area between the Juba and Shabelle rivers, particularly in Baydhabo district. The control method was then shifted to the regular WHO approach of surveillance, containment and ring-vaccination. A reward of 200 Somali shillings was introduced for any new reported smallpox case. Surveillance was intensified. This led to a sharp increase in reported cases in June 1977 – a peak was reached in the middle of July 1977. Then 25 experienced WHO field epidemiologists arrived. I was one of them and was posted to Gedo one of the regions, which still had smallpox. Transmission was gradually brought under control. At the beginning of August, it was clear that transmission mainly consisted of spread between small nomadic groups. These outbreaks were difficult to find and had to be located by temporary searchers sent out on foot. By the end of November there were still five pending outbreaks in Gedo. I give an account of what working in a tough, sometimes hostile area entailed and how we solved the problems encountered there. Those were the last smallpox cases in Gedo. The success was to a large extent dependent on close cooperation with the local people, particularly the camel herders. Without their engagement smallpox would not have been eradicated so quickly in Gedo and thereby not in Somalia.